Simultaneous Production of Sugar and Ethanol from Sugarcane in China, the Development, Research and Prospect Aspects - Liang, Lei; Xu, Riyi; Li, Qiwei; Huang, Xiangyang; An, Yuxing; Zhang, Yuanping; Guo, Yishan (IntechOpen, 2012)
None